Behavior of Leachate of Construction & Demolition Waste C&D and Recycled Aggregates RAs - هيثم شاهين,; عماد فاضل ,; ناجي ديوب, (Tishreen University Journal -Engineering Sciences Series,, 2023)
There is an increased interest in construction & demolition waste C&D, especially, after their large production around the word. In 2018, a total waste generated, in European Union, by all economic activities & households (EU-27) amounted 2713 million tons. While, the construction & demolition waste were formed 37% of total amount. Management the large quantities of C&D waste needs big funding, good infrastructure, and technical support. In addition to study the release of their contaminations and environmental impacts, during the life cycle assessment. Release and leaching from construction & demolition waste, are influenced by several factors, such as chemical & physical properties, collection, storage, transport, and the age of C&D Waste. Experiments to estimate release from the leachate of construction & demolition waste C&D and recycled aggregates RAs, were done, due to leachate tests, in High Institute for Environmental Research & High Institute for Marine Research. The main obtained results showed the following: - PH of construction & demolition waste C&D and recycled aggregates RAs leachate, was exchanged between acidity & alkalinity due to waste age. - Comparing the leaching results with regulatory limits value of MD-186/2006 showed that, SO4, Cu, COD are critical parameters.